Pengaruh Return On Equity (ROE) Terhadap Dividend Payout Ratio (DPR) (Studi Pada Perusahaan Sektor Makanan dan Minuman yang Terdaftar di BEI) - Sulaeman, Maman (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2018)
Companies that have the ability to pay dividends assumed the community as a profitable company. The instability of the House of Representatives was allegedly the result of the fluctuation of ROE. It is reflected from the average ROE of food and beverage companies listed on the BEI in 2008-2012 shows an increase and decrease (fluctuate). The purpose of this research is to know: how much influence Return on equity (ROE) to Dividend Payout Ratio (DPR) at food and beverage sub sector listed on BEI. The research method using verivikatif.Teknik data collection is done through secondary data of financial statements in BEI. The results showed that the Return On Equity (ROE) of food and beverage companies listed on the BEI from 2008 to 2012 generally fluctuate with an average of 17.09%. Dividend Payout Ratio (DPR) food and beverage companies listed on the Stock Exchange from 2008 to 2012 generally berluktuatif with an average of 54.36%. There is a positive influence on Return on Equity (ROE) to Dividend Payout Ratio (DPR) at food and beverage companies listed on BEI in the sense that the greater ROE ratio will be followed by the increase of DPR.